Contribution of Income Tax to GDP in Nepal - Adhikari, Krishna Gopal (Journal of Management, 2020)
This research paper examines the contribution of income tax in revenue generation in Nepal after 2068 to 2073 B.S. The focus of the article is in the area of tax revenue collection. The results obtained from secondary data and information collected from reports, articles and journals. It is based on descriptive research design with the estimate of income tax to revenue generation. This suggests that the ratio of income tax on GDP is increasing every year since study period. Such a study is important in order to estimate contribution of income tax to GDP. The findings help to solve the problems of Income Tax System of Nepal. The main conclusion drawn from this study is the contribution income tax revenue is not sufficient to generate funds of tax revenues. This article recommends that the researchers, government and policy makers who want to know the contribution of income tax revenue to GDP in Nepal.